Spinal Injuries in Children - Basu, Saumyajit (Frontiers in Neurology, 2012)
Spinal injuries in children is a separate entity, quite different from its adult counterpart due to wide differences with regards to anthropometrics, biomechanics, injury patterns, clinical presentation, imaging analysis and management principles. Literature addressing these issues was relatively sparse historically. In more recent years, different aspects of the pediatric spine have been better appreciated and hence there has been a plethora of publications on this area. The typical injuries occurring in children include occipitoatlantal dissociation (Figure 1), atlanto-axial rotary subluxation (Figure 2), spinal cord injury without radiological abnormality (SCIWORA) (Figure 3) and multiple thoracic compression fracture.